Pendampingan Penyusunan SOP Inventory Management System dan Persediaan Barang untuk Meningkatkan Efektivitas Pengelolaan Persediaan pada UMKM Tea Break Purwosari - Fatmasari, Dwi; Saniatur Rohma, Nurus; Laily, Wardah; Putri Agustin, Dita; Nur Hidayat, Ryan (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Inventory management lacking clear operational standards can lead to suboptimal administrative processes and stock control within MSMEs. Preliminary observations at the Tea Break Purwosari MSME revealed that inventory management relied on Microsoft Excel and manual stock checks. Although the business manages approximately 35 types of raw materials and supporting supplies, it lacked written Standard Operating Procedures (SOPs) to guide the processes of receiving, storing, recording, and issuing goods. This community service initiative aimed to assist in developing SOPs for the Inventory Management System and general inventory handling to enhance inventory management effectiveness. The implementation method involved observation, interviews, problem identification, SOP drafting, dissemination, implementation support, and evaluation through observation sheets and discussions with the partner. The results indicate that the developed SOPs provided a more structured operational framework for inventory management. Implementing these SOPs improved administrative orderliness, clarified workflows, and supported more systematic and effective stock control at Tea Break Purwosari.